Peasants and Politics: Re-thinking the British Imaginative Geography of the Balkans at the Time of the First World War. (January 2017) - Perkins, James
This article examines British representations of the Balkans in the late nineteenth and early twentieth centuries. It does so through focusing on records of political activism and humanitarianism, offering a counterpoint to the key studies of this subject in the 1990s that were based primarily on analysis of travel writing and literary texts. The subjectivities of the political culture that inspired engagement with Balkan questions are scrutinized, exposing the complexity of British perspectives on the region and highlighting intersections between international and domestic debates. Attention is drawn in particular to the idealization of Balkan peasant society and the 'village community' in British Liberal political discourse. This is related to tensions around land reform at home, and to the perceived impact of industrialization and urbanization on British society and citizenship. Reassessing the complex imaginative geography of the Balkans in this way provides a fresh transnational perspective on aspects of British domestic political history. It also raises broader arguments about the need to integrate historical analysis of the 'cultural' and 'political' aspects of British encounters with foreign lands and peoples in the era of the First World War.